PERBANDINGAN PERENCANAAN PEMBANGUNAN NASIONAL SEBELUM DAN SESUDAH AMANDEMEN UNDANG-UNDANG DASAR 1945 - Anggraini, Yesi; Yasir, Armen; Ridlwan, Zulkarnain (FIAT JUSTISIA, 2015)
Comparing national development planning as the state policy in the broad outlines in the period before and after the amendment of the Constitution 1945 (UUD 1945) as well as to analyze the position of national development planning guidelines were created after the amendment of the Constitution 1945. Based normative juridical approach, by examining all the rules legislation relating to the legal issues is researched concluded that the First, there are some similarities and differences in the Platform for National Development Planning in the period before and after the 1945 amendment, as for the equation is the substance of the two, whereas the difference lies in the pattern of policy-making, as well as law formulation. Second, the Status Law on National Development Planning System (SPPN) and the regulations under it is official documents which contain the cornerstone of development planning in the era of reforms as a change of planning from documents in the past.Keywords: National Development Planning System, the Constitution 1945